Lift distribution of washout twist morphing MAV wing - I. Ismail, N.; Yusoff, H.; Sharudin, Hazim; Pahmi, Arif; Hafi, H.; M.M, Mahadzir (International Journal of Engineering and Technology, 2018)
Micro Air Vehicle, or also commonly known as MAV, is a miniature aircraft that has been gaining interest in the industry. MAV is defined as a flying platform with 15cm wingspan and operates at a speed of around 10m/s. Recently, MAV has been exposed with the latest development and link towards the biologically-inspired designs such as morphing wing. Twist morphing wing is one of the latest MAV wing design developments. The application of Twist Morphing (TM) on MAV wing has been previously known to produce better aerodynamic performance. Previous study in washin TM wing has shown a promising possibility of generating higher lift force. Despite the benevolent performance exhibited by the washin TM wing, the lift distribution for the washout type of TM MAV is relatively unknown and still open to be explored. This is probably due to the lack of experimental test rig to produce the washout twist morphing motion on the MAV wing. Therefore, this research aims to produce a special test rig for washout TM wing that is compatible for wind tunnel experimental testing. By using the special test rig, the experimental investigation on the lift performance of washout TM MAV wing can be done. Based on the wing deformation results, it clearly shows that the proposed test rig is capable to produce up to 19.5mm tip deflection at the morphing point, which is also resulting in a significant morphing motion. Higher morphing force induces larger morphing motion. Based on the lift distribution results, they show that the morphing motion has significantly affected the overall lift distribution on the MAV wing. The morphing motion on TM wing has produced at least 17.6% and 5.33% lower CL and CLmax magnitude, respectively, with the membrane wing especially at the pre-stall region. However, the TM wing is still able to maintain the stall angle similar to the baseline wing at Î±stall= 31Â°. By maintaining high Î±stall value with lower CL and CLmax magnitude, TM wing produces more agility for the MAV maneuverability that will be useful for indoor mission or obstacle avoidance flight.Â Â